Woningbouw wereldwijd betaalbare woningen voor groeiende steden = Global housing : affordable dwellings for growing cities - Andel, Frederique van 1971-; Gameren, Dick van 1962- (DASH: Delft architectural studies on housing, 2015)
In the emergent economies, the acute shortage of affordable housing is responsible for a gigantic building production, which is not without its problems. Standard solutions are applied on a large scale that seem to bypass local cultural practices. The import in Africa of mass housing models from abroad is an example of this. DASH Global Housing explores the field of tension between the desired mass production and solutions that are tailored to local conditions. How can new megacities do justice to existing social and economic structures, local production techniques and individual housing preferences? What is the standard and what the ideal? DASH Global Housing includes essays by Tom Avermaete and Nelson Mota, and interviews with Balkrishna Doshi and Go West. The planning documentation presents projects by Charles Correa, Elemental, Hassan Fathy and others